Failure analysis of a steel pressure vessel with a composite wrap repair proposal. (October 2021) - Vukelic, Goran; Vizentin, Goran; Bakhtiari, Reza
Abstract: Two steel pressure vessels, part of an air compressor unit, failed during hydrostatic test at a pressure lower than proof pressure. Pressure drop and fluid leakage was noted during the test and later investigation revealed through-wall cracks on the shells of each vessel. Experimental and numerical investigation was employed to determine possible causes of failure and to propose a repair method for such vessels. Non-destructive testing (visual and ultrasonic) was performed to check the outer and inner surfaces of the vessel for possible cracks and to measure wall thickness. Optical and scanning electron microscopy was used to inspect crack surroundings and determine the size of the cracks. According to experimentally obtained results, excessive pitting corrosion at the bottom part of the vessel initiated cracks. In order to retain the functionality of the vessel, composite patch repair procedure is proposed. Numerical analysis was performed to determine pressure bearing capacity of the repaired vessel. Also, recommendations for avoidance of failure scenario for considered pressure vessels are given. Highlights: Steel pressure vessel failed during hydrostatic test. Experimental failure analysis was performed. Failure was caused by pitting on the lower part of inner wall of the vessel. Finite element analysis was performed to assess the possibility of composite wrap repair. Results showed that the composite repair is capable of withstanding test pressure.